Life prediction of 6201-T81 aluminum alloy wires under fretting fatigue and variable amplitude loading. (May 2023) - Matos, I.M.; Araújo, J.A.; Castro, F.C.
Abstract: Fretting fatigue tests under variable amplitude loading were performed on 6201-T81 aluminum alloy wires of an AAAC 900 MCM conductor. The loading program consisted of a three-block loading history, defined using vibration data of a transmission line located in the center-west region of Brazil. Two previously developed methodologies for life prediction of wires under fretting fatigue, based on the Theory of Critical Distances and on a master fatigue curve, were extended to variable amplitude loading conditions. The good agreement between measured and predicted lives indicated that both methodologies can be useful for fatigue analysis of wires of overhead conductors.